1990
DOI: 10.1002/j.1460-2075.1990.tb07391.x
|View full text |Cite
|
Sign up to set email alerts
|

Topography of intermediates in transcription initiation of E.coli.

Abstract: Three characteristic footprinting patterns resulted from probing the Escherichia coli RNA polymerase T7 A1 promoter complex by hydroxyl radicals in the temperature range between 4 degrees C and 37 degrees C. These were attributed to the closed complex, the intermediate complex and the open complex. In the closed complex, the RNA polymerase protects the DNA only at one side over five helical turns. In the intermediate complex, the range of the protected area is extended further downstream by two helical turns. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

22
140
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(162 citation statements)
references
References 36 publications
22
140
0
Order By: Relevance
“…To our knowledge, the conserved sequence TCCC in both species has not been previously identified in any other a7O promoter (i.e., other than rRNA promoters and some tRNA promoters), and its presence raises the possibility of an additional regulatory determinant that may be important for these by the heat shock sigma factor cr32 (9). These nucleotides are in close contact with the RNA polymerase during open complex formation at the start of transcription (41), which is why this conserved sequence might be important in some aspect of the regulation which is similar in the trmA and rrn promoters. Dickson et al (12) and Gaal et al (15) have changed two of the four bases in the TCCC sequence of rrnB P1, resulting in TTCC (C-17T) and CCCC (T-18C).…”
Section: Discussionmentioning
confidence: 87%
“…To our knowledge, the conserved sequence TCCC in both species has not been previously identified in any other a7O promoter (i.e., other than rRNA promoters and some tRNA promoters), and its presence raises the possibility of an additional regulatory determinant that may be important for these by the heat shock sigma factor cr32 (9). These nucleotides are in close contact with the RNA polymerase during open complex formation at the start of transcription (41), which is why this conserved sequence might be important in some aspect of the regulation which is similar in the trmA and rrn promoters. Dickson et al (12) and Gaal et al (15) have changed two of the four bases in the TCCC sequence of rrnB P1, resulting in TTCC (C-17T) and CCCC (T-18C).…”
Section: Discussionmentioning
confidence: 87%
“…1). The RPc, which is usually unstable and competitor sensitive, gives an abbreviated protection footprint that does not include DNA downstream of the transcription start site (7,9,10). Creation of the stable polymerase/promoter open complex (Rpo) requires bending and unwinding of the DNA (11) and major conformational changes (isomerization) of the polymerase (Fig.…”
mentioning
confidence: 99%
“…1 A) (12)(13)(14). The result of these changes generates a complex in which the promoter is unwound from Ϫ11 to around ϩ3, and the protection footprint extends to around ϩ25 (9,11,(15)(16)(17)(18)(19)(20)(21). In addition, RPo is normally competitor resistant, although RPo at the very strong ribosomal promoters does not follow this rule (22,23).…”
mentioning
confidence: 99%
“…Kinetic studies on the formation of an RNA polymerasepromoter complex revealed the presence of a sequence of isomerization steps leading to the formation of an open complex (16)(17)(18). Furthermore, by decreasing the isomerization rates at lower temperatures, one or more intermediates in the pathway from the initial closed complex to the final open complex were isolated and characterized (19)(20)(21)(22). However, the large, and sometimes nonlinear, temperature dependence of some of the steps in this pathway (16,18,23) and the occurrence of intermediates at low temperatures that were not detected on the normal kinetic pathway (21) suggest that the structure of intermediates and͞or the mechanism of promoter recognition and DNA opening could differ at low temperatures compared with normal physiological conditions.…”
mentioning
confidence: 99%